The Needs for Visual Improvement of Patients Presented at Low-Vision Center in Wenzhou, China - Xiaoman Li; Guofu Chen; Ruzhi Deng; Na Lin; Lingzhi Ni; Longfei Jiang; Haishuang Lin; Frank Thorn; Jie Chen (Journal of Ophthalmology)
Purpose. To characterize the needs for visual improvement of new-visit patients with low vision. Methods. This cross-sectional study collected detailed information of patients presented at low-vision center of the Eye Hospital of Wenzhou Medical University between January 2015 and January 2017. A questionnaire interview, including demographic information and needs for visual improvement, was conducted before ophthalmology examinations. Results. The main need for visual improvement was engagement in hobbies (68.9%), followed by reading (20.9%), engaging in occupation (20.1%), and watching TV or movies (17.1%). Less than 10% of patients mentioned the demand of using public transportation (5.8%), doing housework (3.7%), writing (1.9%), walking on irregular surfaces (1.5%), driving (1.1%), and others (2.4%). Women were significantly associated with a concern for performing hobbies (OR 1.45, 95% CI 1.0–2.0) but associated with lower odds of reading (OR 0.46, 95% CI 0.3–0.7). Older subjects were more willing to choose hobbies (OR 1.35 (per 10-year increase), 95% CI 1.3–1.4), reading (OR 1.11 (per 10-year increase), 95% CI 1.0–1.2), watching TV or movies (OR 1.4 (per 10-year increase), 95% CI 1.3–1.6), and housework (OR 1.21 (per 10-year increase), 95% CI 1.0–1.5) than younger individuals. In comparison with younger participants, older individuals were less likely to choose occupation (OR 0.53 (per 10-year increase), 95% CI 0.5–0.6). No significant association was found between visual acuity and needs for visual improvement. Conclusion. Hobbies, reading, engaging in occupation, and watching TV were the most common needs for visual rehabilitation in patients with visual impairment. Gender and age showed a modest influence on the choice of different needs.